Illustrations and Analysis of Disclosures of Pension Information (Book). - Meyer, Philip E.; Stone, Mary S. (The Accounting Review, 1982)
Reviews the book "Illustrations and Analysis of Disclosures of Pension Information," by Hortense Goodman, Frank C. Munn, Anthony Phillips and Miklos Vasarhelyi.